2021
DOI: 10.1093/scan/nsaa167
|View full text |Cite
|
Sign up to set email alerts
|

Context-based interpersonal relationship modulates social comparison between outcomes: an event-related potential study

Abstract: Social comparison is a common behavior that largely determines people’s experience of decision outcome. Previous research has showed that interpersonal relationship plays a pivotal role in social comparison. In the current study, we investigated whether the manipulation of context-based relationship would affect participants’ comparison of self-outcome and other-outcome. Participants first finished a trust game with likeable (dislikeable) partner and then they were involved in a gambling task and observed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 116 publications
1
21
1
Order By: Relevance
“…Boksem et al (2011) showed that differential P300 responses between self-related positive and negative feedback were smaller when others obtained positive feedback than when others obtained negative feedback. When participants gained an amount of money, the RewP and LPP responses were more positive for others' gains than for others' losses; however, this effect was not shown when participants lost money (Zhang et al, 2020(Zhang et al, , 2021.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Boksem et al (2011) showed that differential P300 responses between self-related positive and negative feedback were smaller when others obtained positive feedback than when others obtained negative feedback. When participants gained an amount of money, the RewP and LPP responses were more positive for others' gains than for others' losses; however, this effect was not shown when participants lost money (Zhang et al, 2020(Zhang et al, , 2021.…”
Section: Introductionmentioning
confidence: 80%
“…Based on previous studies (e.g., Hu et al, 2017;Liu et al, 2020;Marco-Pallarés et al, 2010;Rigoni et al, 2010;Qi et al, 2018;Wu et al, 2012;Zhang et al, 2020Zhang et al, , 2021 and visual inspection of grand waveforms, ERPs were quantified using the mean amplitudes for P200 (190-260 ms), RewP (290-360 ms), P300 (360-420 ms) and LPP (420-750 ms) components. The P200 and RewP components were measured at the Fz and FCz electrodes.…”
Section: Eeg Recordings and Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…While the P3 has been related to diverse cognitive operations [ 107 , 108 ], many studies suggest that this component is closely associated with a motivational level in decision-making tasks, such that a larger P3 indicates the stronger motivational significance of the ongoing event [ 56 , 71 , 109 111 ]. For instance, a larger P3 was observed when participants were comparing their task performance with that of a disliked opponent’s, indicating stronger motivation to outperform that opponent [ 112 ]. Given this background knowledge, we propose a possible interpretation of the P3 finding: compared to the controls, mild depressive individuals’ motivation to provide better performance in a social scenario is less likely to be modulated by their expectation of receiving positive social feedback (or avoiding negative social feedback) from a human companion.…”
Section: Discussionmentioning
confidence: 99%
“…4.6. Posterior-parietal late positive component LPC is another ERP component closely related to relevant motivational stimuli and the subsequent sustained allocation of attention [56,57,126], and to the saliency of an outcome also in social comparisons [127][128][129]. Recent evidence provided by the analysis of a modified Dictator Game exploring the role of players' social status [40] revealed that LPC amplitude was more sensitive to the interaction of the recipient's status and fairness -i.e., with a tendency of greater amplitude triggered by unfair endowment shares for a high-status Recipient and greater amplitude triggered by fair splits for a medium-status Recipient.…”
Section: Medial Frontal Negativitymentioning
confidence: 99%